Boosting the MHC Class II-Restricted Tumor Antigen Presentation to CD4+ T Helper Cells: A Critical Issue for Triggering Protective Immunity and Re-Orienting the Tumor Microenvironment Toward an Anti-Tumor State - Accolla, Roberto; Lombardo, Letizia; Abdallah, Rawan; Raval, Goutham; Forlani, Greta; Tosi, Giovanna (Frontiers in Oncology, 2014)
Although the existence of an immune response against tumor cells is well documented, the fact that tumors take off in cancer patients indicates that neoplastic cells can circumvent this response. Over the years many investigators have described strategies to rescue the anti-tumor immune response with the aim of creating specific and long lasting protection against the disease. When exported to human clinical settings, these strategies have revealed in most cases a very limited, if any, positive outcome. We believe that the failure is mostly due to the inadequate triggering of the CD4+ T helper cell (TH) arm of the adaptive immunity, as TH cells are necessary to trigger all the immune effector mechanisms required to eliminate tumor cells. In this review we focus on novel strategies that by stimulating MHC class II-restricted activation of TH cells generate a specific and persistent adaptive immunity against the tumor. This point is of critical importance for both preventive or therapeutic anti-tumor vaccination protocols, because adaptive immunity with its capacity to produce specific, long lasting protection and memory responses, is indeed the final goal of vaccination. We will discuss data from our as well as other laboratories which strongly suggest that triggering a specific and persistent anti-tumor CD4+ TH cell response stably modify not only the tumor microenvironment but also tumor-dependent extratumor microenvironments eliminating and/or reducing the blood-derived tumor infiltrating cells that may have a pro-tumor growth function such as regulatory CD4+/CD25+ T cells (Tregs) and myeloid-derived suppressor cells (MDSC). Within this frame therefore, we believe that the establishment of a pro-tumor environment is not the cause but simply the consequence of the tumor strategy to primarily counteract components of the adaptive cellular immunity, particularly TH lymphocytes.